GAMBARAN FAKTOR RISIKO KECACATAN PADA PENDERITA KUSTA - Widya, Tiya Nur; Adi, Mateus Sakundarno; Martini, Martini (Jurnal Kesehatan Masyarakat (Undip), 2019)
Leprosy is an infectious disease that can cause physical disability of patient. Based on data proportion of level 2 is 14%.Govermnet policy ,tolerance of limit disability in an area may not ≥5%. This research aims to describe the proportion of disability status in leprosy and describe to risk factor. This research 144 leprosy patients in Pemalang area. Variable subjects covering age, sex, kinds of work, the level of education, way discovery, type leprosy and the level knowledge of leprosy by the patients. These research use observational descriptive approach by cross sectional. The descriptive data set in the form of tabulation cross. The analysis that the proportion of disability 27,9%.The proportion among of respondents age more  than of 14 years was 29,0%, male of 28,7 %. In the low of educational level  34,9 %. Patient as a farmer  30,42%, MB leprosy type was 29,0%. Low knowledge of leprosy 33,7% and discovery of 28,1 % voluntary or passive .The conclusion was disability was higher for the proportion of respondents with age more than 14 years , male, a low of education level, low of knowledge, farmers workers, MB type, and the passive leprosy. Suggested the research to analytic analysis was conducted